2022
DOI: 10.1039/d1tc03837k
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed self-powered near-infrared photodetectors of toxic heavy metal-free AgAuSe colloidal quantum dots

Abstract: Self-powered, high detectivity, solution-processed near-infrared (NIR) quantum dot photodetectors based on novel alloyed AgAuSe quantum dots (QDs) are fabricated for the first time and their photoelectric properties are explored. AgAuSe...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“… ,, Strikingly, it also exceeds those of self-powered PDs in most previous works (Figure e and Table S1). It should be noted that D* values for our devices are estimated based on the noise current measurement (Figure e), which should be smaller than D * determined based on the dark current. The noise current plays an important role in the capability of photodetectors to detect weak light signals .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“… ,, Strikingly, it also exceeds those of self-powered PDs in most previous works (Figure e and Table S1). It should be noted that D* values for our devices are estimated based on the noise current measurement (Figure e), which should be smaller than D * determined based on the dark current. The noise current plays an important role in the capability of photodetectors to detect weak light signals .…”
Section: Resultsmentioning
confidence: 84%
“…(d) Cross-sectional TEM image of the Cu–In–Se QD-PDs. (e) Comparison of our work with self-powered QD-PDs in previous works, in regard to the maximum detectivity and the thickness of the light absorption layer. Self-powered PDs based on other materials from recent literature are shown together for comparison. (f) Photograph of the flexible Cu–In–Se QD-PD attached on a needle.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[55] Besides, in 2022, Wu et al reported a novel self-powered NIR photodetector and investigated the AgAuSe QDs photodetector device performances and its device physics for the first time (Figure 3a). [56] Compared to HgTe QDs, the origin, and theory of Ag-based QDs photodetector are still in the infancy stage. Ag-based QDs can profit significantly from systematic studies and further improvement in synthesis and characterization.…”
Section: Non-toxic Quantum Dotsmentioning
confidence: 99%
“…In contrast, self-powered devices driven by the photovoltaic effects in heterojunctions, Schottky junctions, and organic/inorganic hybrid junctions, rapidly separate electron–hole pairs under the influence of built-in electric fields leading to increased photosensitivity and faster switching speed, all without relying on external energy sources. Consequently, self-powered photodetectors have gained significant limelight in recent years. ,,,,, …”
Section: Introductionmentioning
confidence: 99%